2004
DOI: 10.1096/fj.04-1807fje
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic phospholipase A2mediates neuronal apoptosis induced by soluble oligomers of the amyloid‐β peptide

Abstract: Recent data have revealed that soluble oligomeric forms of amyloid peptide (Abeta) may be the proximate effectors of the neuronal injury and death occurring in Alzheimer's disease (AD). However, the molecular mechanisms associated with the neuronal cell death induced by the nonfibrillar Abeta remain to be elucidated. In this study, we investigated the role of the cytosolic Ca2+-dependent phospholipase A2 (cPLA2), and its associated metabolic pathway, i.e., the arachidonic acid (AA) cascade, in the apoptotic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
112
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 42 publications
16
112
2
Order By: Relevance
“…As expected from our previous reports Garcia et al, 2010;Kriem et al, 2005;Malaplate-Armand et al, 2006), the incubation of cortical neurons of WT mice with 1 or 5 M A␤ 42 oligomers for 24 hours resulted in a 40%-50% decrease in cell viability (Fig. 5A), whereas 1 M A␤ 42 induced a 5-fold increase in apoptotic nuclei number, as compared with untreated WT neurons (Fig.…”
Section: Cpla 2 ϫ/ϫ Neurons Are Resistant To Soluble A␤ Oligomer-indusupporting
confidence: 87%
See 3 more Smart Citations
“…As expected from our previous reports Garcia et al, 2010;Kriem et al, 2005;Malaplate-Armand et al, 2006), the incubation of cortical neurons of WT mice with 1 or 5 M A␤ 42 oligomers for 24 hours resulted in a 40%-50% decrease in cell viability (Fig. 5A), whereas 1 M A␤ 42 induced a 5-fold increase in apoptotic nuclei number, as compared with untreated WT neurons (Fig.…”
Section: Cpla 2 ϫ/ϫ Neurons Are Resistant To Soluble A␤ Oligomer-indusupporting
confidence: 87%
“…We previously reported that soluble A␤ oligomers caused early calcium-dependent release of AA associated with a transient relocalization of cPLA 2 to the plasma membrane, suggesting that activation of cPLA 2 and subsequent release of AA are critical steps for soluble A␤ oligomermediated apoptosis in cortical neurons. We confirmed this hypothesis by using antisense oligonucleotides and pharmacological inhibitors of cPLA 2 that abolished AA release and protected neurons against A␤-induced apoptosis (Kriem et al, 2005). Furthermore, we demonstrated that activation of cPLA 2 by A␤ oligomers precedes that of sphingomyelinases (SMases) and subsequent production of ceramides associated with neuronal apoptosis .…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In vitro studies also showed that a high dose of Ab-42 induced neuronal degeneration and neurapophysis retraction (Pike et al, 1992;Dahlgren et al, 2002). Recent data indicates that neuronal injuries and death have been correlated with the status of Ab-42 (Sponne et al, 2004;Kriem et al, 2005). Despite there are studies suggesting the role of soluble Ab-42 in promoting the growth of neurapophysis and enhancing neuron survival in a short time, other researches has shown that soluble Ab-42 oligomers may be the proximate effectors of AD and that Ab-42 in soluble oligomeric status can induce neuronal death (Gong et al, 2003;Kim et al, 2003;Florent et al, 2006).…”
Section: Discussionmentioning
confidence: 99%